Pyrosequencing: methods and protocols - Lehmann, Ulrich; Tost, Jörg (Methods in molecular biology, 2015)
The History of PyrosequencingÒ -- Pyro Mark® Instruments, Chemistry and Software for Pyrosequencing® Analysis -- Software-Based Pyrogram® Evaluation -- Quantitative Validation and Quality Control of Pyrosequencing® Assays -- Extended KRAS and NRAS Mutation Profiling by Pyrosequencing® -- Universal BRAF State Detection by the Pyrosequencing®-based U‑BRAFV600 Assay -- Pyrosequencing®-based Identification of Low Frequency Mutations Enriched through Enhanced-ice-COLD-PCR -- Analysis of Mutational Hotspots in Routinely Processed Bone Marrow Trephines by Pyrosequencing® -- Analysis of Copy Number Variation By Pyrosequencing® using Paralogous Sequences -- Prenatal Diagnosis of Chromosomal Aneuploidies by Quantitative Pyrosequencing® -- HLA-B and HLA-C Supratyping by Pyrosequencing® -- Allele Quantification Pyrosequencing® at Designated SNP sites to Detect Allelic Expression Imbalance and Loss-of-heterozygosity -- Quantitative DNA Methylation Analysis by Pyrosequencing® -- Quantitative Methylation Analysis of the PCDHB Gene Cluster -- Assessment of Changes in global DNA Methylation Levels by Global Analysis of DNA 5-methylcytosine using the Luminometric Methylation Assay, LUMA -- Limiting Dilution Bisulfite Pyrosequencing®: a Method for Methylation Analysis of Individual DNA Molecules in a Single or a Few Cells -- Detection of Loss of Imprinting by Pyrosequencing® -- Analysis of DNA Methylation Patterns in Single Blastocysts by Pyrosequencing® -- Allele-specific DNA methylation detection by Pyrosequencing® -- SNP-based Quantification of Allele-Specific DNA Methylation Patterns by Pyrosequencing® -- DNA Methylation Analysis of ChIP Products at Single Nucleotide Resolution byPyrosequencing® -- Multiplex Pyrosequencing®: Simultaneous Genotyping Based on SNPs from Distant Genomic Regions -- Detection of Drug-Resistant Mycobacterium tuberculosis -- Application of Pyrosequencing® in Food Biodefense -- Forensic Analysis of Mitochondrial and Autosomal Markers using Pyrosequencing® -- Tissue-specific DNA Methylation Patterns in Forensic Samples Detected By Pyrosequencing®.